Processos de resiliência em crianças diagnosticadas com câncer: uma revisão sistemática de literatura - Santos, Viviana Lanfranchi (Universidade Federal de São Carlos, 2022)
Children and adolescents diagnosed with cancer experience several stressors, whether physical, psychological, social and/or spiritual, which can be characterized as risk factors for the development and quality of life of these individuals. Resilience can be observed in several patients with this diagnosis and constitutes an important coping mechanism in the process of becoming ill. Resilience processes can be facilitated by carrying out interventions, and actions of this magnitude can become protective factors throughout the course of the disease. Therefore, the objective of this investigation was to carry out a systematic review of the literature to understand how the phenomenon of resilience is studied in children and adolescents with cancer diagnosis and treatment. In the first study, the methodological strategies of investigation with this population were emphasized. In the second study, the aim was to characterize the interventions, documented and scientifically validated, that promote resilience in the aforementioned group. For that, the guidelines of the PRISMA protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) were used. The following databases were chosen: PUBMED, PsycINFO, SciELO, PePSIC, LILACS and IndexPsi. No time intervals were defined for the searches and the selected publications were written in Portuguese, Spanish and English. After the search, the inclusion and exclusion criteria were applied, selecting 31 and 6 articles, respectively, to compose the analysis corpus of the first and second studies. The analysis of the articles in the samples was carried out based on previously defined thematic categories. Methodologically, there was a predominance of quantitative research with a cross-sectional design, which can limit the view on a phenomenon as complex as resilience. Despite this, a diversity was identified in the instruments used to study it, in order to cover various constructs associated with resilience and the context of children and adolescents with cancer. Only two interventions focused on this population were identified, which shows an area still little explored, given the great existing demand of this group of people. Even in small numbers, the interventions studied proved to be very effective in improving the quality of life of the children and adolescents participating in the research, as well as in the resilience shown by them. All the studies analyzed have significant limitations, usually related to the representativeness of the sample and the generalizability of the results.
Processes of resilience in children diagnosed with cancer: a systematic literature review
Keywords: Revisão sistemática; Resiliência; Método; Intervenção; Crianças; Adolescentes; Câncer; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO